The effect of cushion properties on skin temperature and humidity at the body-support interface. - Hsu, Tzu-Wen; Yang, Shu-Yu; Liu, Jung-Tai; Pan, Cheng-Tang; Yang, Yu-Sheng (Assistive Technology, 2018)
The purpose of this study is to explore the effects of various cushions on skin temperature and moisture at the body--seat interface during a 2-hour period of continuous sitting. Seventy-eight participants were randomly assigned to sit on one of the three types of wheelchair cushions for unrelieved sitting for over 2 hours. Skin temperature and relative humidity (RH) were measured under the subjects' ischial tuberosities and thighs bilaterally with digital temperature and humidity sensors. Data were collected before sitting and at 15-minute intervals thereafter. Participants sitting on foam--fluid hybrid cushions showed significantly lower skin temperatures than those sitting on air-filled and foam cushions (p < 0.05), but RH did not differ significantly among the cushions (p = 0.97). The three cushions produced a similar increasing trend in RH over time and RH reached a plateau during the 2-hour sitting period. To select the appropriate wheelchair cushion, the microclimate (heat and moisture control) between the body--seat interface should be considered aswell as pressure distribution. In comparison with foam--fluid hybrid cushions, the air-filled rubber and foam cushions tended to increase skin temperature by several degrees after prolonged sitting. However, cushion materials did not have significant differences in moisture accumulations.